THE DECREASE OF SODIUM CHLORIDE CONSUMPTION. EFFICACY OF PREVENTIVE STRATEGY. PART V - N. G. Poteshkina (Российский кардиологический журнал, 2014)
The article concerns the review of different approaches to reduce table salt consumption by human beings. The levels for harmless consumption are reviewed those were recommended in terms of target organ damage prevention. The guidelines for salt consumption consuming regulation are presented, that are in use in various world countries. The foundations for personal, social aEnd state policy for practical implication of these guidelines are provided. The predicted outcomes for the realization of the policy in relation to decrease of general and cardiovascular mortality and also correction of arterial hypertension are given. The article can be in the field of interest of physicians — internists of broader profile, cardiologists, health managers.